Suicide ideation in older people: a qualitative review and Meta-aggregation of Asian studies - Christensen, Martin; Chan, Hiu Yin; Chan, Yuen Yi; Cheng, Ka Yee; Cheung, Tsz Yan; Li, Tsz Yan; Situ, Jia Ling; Tam, Po Lam; Tse, Cheuk Chi; Ma, Haixia (Frontiers in Psychiatry, 2023)
To appraise and synthesise qualitative studies examining older Asian people's experiences of suicidal ideation.Four databases were accessed to retrieve papers published between 1990 and 2022 including the grey literature, hand-searching of reference lists of retrieved papers and key journals. The phenomenon of interest included participants older than 60 years old, must have experienced a form of suicidal ideation and/or an unsuccessful attempt, had actively thought about harming themselves and be of Asian ethnicity.This review was conducted according to Consolidated Criteria for Reporting Qualitative Research and the Joanna Briggs Institute's System for the Unified Management of the Assessment and Review of Information.Of the 289 potential studies, seven papers met the inclusion criteria. Two synthesised findings resulted from this review -The Suffering Situation: A Life without Meaning in Older Age and The Healing Situation: A Life Worth Living. The experiences of older Asian people varied from feelings of loneliness, despair and isolation to wanting to live a fruitful life into old age.Suicidal ideation in the older person is a growing concern especially with the rise in suicide in this age group. Rising health care costs, erosion of traditional family values means that the older person views themselves as a burden. However, because of the limited number of qualitative studies from an Asian perspective it is difficult to ascertain the full extent of the issues surrounding suicide in older people.